In-silico prediction analysis of polyphenolic contents of ethanolic extract of Moringa oleifera leaves - Adamu, Umar Muhammad; Renggasamy, Ramesh; Stanslas, Johnson; Abdull Razis, Ahmad Faizal; Mohd Fauzi, Fazlin; Mardi Mulyani, Sri Wigati; Ramasamy, Rajesh (UPM Press, 2023)
Introduction: Moringa oleifera is widely consumed as a source of nutrients and as traditional medicine for treating myriads of diseases in Southeast Asia, Africa, and South America. Polyphenols are abundantly found in the leaves of Moringa oleifera, particularly astragalin and quercetin, and have shown antioxidant and anti-inflammatory activities. In the present study, the polyphenols in Moringa oleifera leaves were identified and quantified, followed by in-silico pharmacokinetics prediction. Methods: Moringa oleifera ethanolic leaf extract (MOEE) was prepared by macerating dry powdered leaves of Moringa oleifera in 70 ethanol, then subjected to ultra-high-performance liquid chromatography-mass spectrometry (UPHLC-MS/MS) to identify polyphenols and quantification by HPLC. In-silico pharmacokinetic prediction analysis of the polyphenols was performed using the SwissADME web tool. Results: Eight polyphenols were identified, among which astragalin and quercetin were quantified. In-silico prediction analysis using SwissADME demonstrates the drug-likeness of the polyphenols in MOEE based on their physicochemical and ADME (absorption, distribution, metabolism and excretion) properties. MOEE contains polyphenols that can serve as lead compound to developing drugs, but only some are predicted to have high GI absorption index demonstrating their utility in oral medication drug development. Moreover, all the polyphenols determined in this study are predicted to be non-brain permeant, demonstrating their limited utility in developing drugs that target brain-related pathologies. Conclusion: Eight polyphenols were identified by UHPLC/MS analysis of Moringa oleifera leaves. Their ADME pharmacokinetics properties predicted some of the polyphenols as favourable candidates for drug development and lead optimisation, thus positioning the Moringa oleifera as an important source of small molecules for drug development.